A Model of Add-On Pricing* - Ellison, Glenn (Quarterly Journal of Economics, 2005)
This paper examines a competitive model of add-on pricing, the practice of advertising low prices for one good in hopes of selling additional products (or a higher quality product) to consumers at a high price at the point of sale. The main conclusion is that add-on pricing softens price competition between firms and results in higher equilibrium profits.